"The missionaries have arrived again": appropriations and reconfigurations of the missions in Ibero-America (1920–1960). - Reisin, Pamela (Paedagogica Historica, 2026)
This article presents the author's research into the meanings acquired by the term missions in the history of education in Ibero-America, its colonial origins and its appropriation and reconfiguration by different political officials, pedagogues and rural teachers. The word "missions" has been used to refer to various practices, both religious and secular. This work will focus on analysing the missions that had the purpose of intervening in non-urban, peripheral territories, far from the centres of political power. In the early 1920s in Mexico, Vasconcelos, then Secretary of Public Education, drew inspiration from the religious missions deployed during the colonial period in Indigenous territories to create Cultural Missions. Between 1930 and 1960, in Spain, Uruguay, Argentina and Brazil, missions were implemented, which shared features with the Mexican experience. What educational concepts and practices were associated with Cultural Missions? Which elements became transnational and why? What role did UNESCO and CREFAL play in this process? To answer these questions, contributions from the transnational history of education, intellectual history and post-colonial studies will be gathered, also relying on various sources, such as mission chronicles, official publications, writings by teachers and officials, and an interview with a missionary.